0
$\begingroup$

Kindly help in Simplifying Y = BCD + BC'D.

I have been trying to simplify the expression for sometime now, using the the 10 rules but cannot simplify fully.

$\endgroup$
0
$\begingroup$

Using the distributive property \begin{align} Y = BCD + BC'D = BD(C + C') \end{align} Since $C + C'$ is always true \begin{align} Y = BD(C + C') = BD(1) = BD \end{align} Therefore $Y = BD$.

$\endgroup$
  • $\begingroup$ I appreciate the assistance. Thank you $\endgroup$ – mandan Nov 21 '15 at 5:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.